KEWENANGAN PEMERINTAH ACEH DALAM KERANGKA OTONOMI DAERAH - Adam Sani (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
The purpose of this study was to determine the authority given by the central government through the Regional Autonomy Law to the Government of Aceh and the extent of the authority of the Aceh government in the implementation of regional autonomy. This type of research uses normative juridical method, the main data source in this study consists of primary legal materials, secondary legal materials and tertiary legal materials. Data collection was carried out through literature study, namely the search of library materials, which included primary legal material in the form of provisions mentioned in the legislation, secondary legal materials in the form of literature books relating to the problem under study. Analysis of primary and secondary data obtained from analytical descriptive research with a normative juridical approach is carried out qualitatively. The results of the study, namely the birth of a special autonomy status for the Aceh region, have eroded some of the authority that is the authority of the central government. The central government is only fully authorized on several matters, namely defense and security, religion, fiscal, education and foreign policy. Apart from this authority, the local government can do this. The implementation of the special autonomy law for the Aceh region with the birth of Law Number 11 of 2006 indicates that the implementation of autonomy is fully held by the region. All matters that become government affairs are further regulated in the Aceh Government law. It is suggested to the government in terms of determining the policy of making the laws of the next regional government so that more attention to all aspects of the affairs of the regional government and the nature of the regulation must be absolute decentralization. It is also advisable to the government to pay special attention to regions with special autonomy status such as Aceh, and it is expected that all implementing regulations which have been obstacles for Aceh in carrying out Aceh's authority can be realized properly. Keywords: Authority, Aceh government, regional autonomy.